2012
DOI: 10.1186/2008-2231-20-84
|View full text |Cite
|
Sign up to set email alerts
|

The effect of semelil (angipars®) on bone resorption and bone formation markers in type 2 diabetic patients

Abstract: Background and purpose of the studyDiabetes mellitus has been recognized as a major risk factor for osteoporosis in which bone turnover is affected by different mechanisms. As the morbidity, mortality and financial cost related to osteoporosis are expected to rise in Iran in coming years, and considering the efficacy of Angipars® for improvement of different ulcers which made it a new herbal drug in diabetic foot ulcer, there is a need to evaluate the effect of this new drug on different organs including bone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
(22 reference statements)
2
4
0
Order By: Relevance
“…These results indicated that diabetes decreased bone formation. This result is in accordance with those obtained by Abd El-Ghfar (2016) and Hasani-Ranjbar et al (2012) who observed lower level of osteocalcin at diabetic groups compared with control group. Sultan et al (2008) observed lower level of osteocalcin in both diabetic groups (patients who were overweight, with type 2 diabetes) compared with control group.…”
Section: Serum Osteocalcin Concentrationsupporting
confidence: 93%
See 1 more Smart Citation
“…These results indicated that diabetes decreased bone formation. This result is in accordance with those obtained by Abd El-Ghfar (2016) and Hasani-Ranjbar et al (2012) who observed lower level of osteocalcin at diabetic groups compared with control group. Sultan et al (2008) observed lower level of osteocalcin in both diabetic groups (patients who were overweight, with type 2 diabetes) compared with control group.…”
Section: Serum Osteocalcin Concentrationsupporting
confidence: 93%
“…The results indicated that diabetes significantly increased serum ALP activity. These results agree with Hasani-Ranjbar et al (2012) who observed that bone serum alkaline phosphatase activities significantly higher with diabetic groups (diabetic patients with chronic disease such as chronic renal failure and diabetic patients) compared with control group. Sultan Entessar et al (2008) showed that PTH level in all diabetic patients was correlated positively with ALP level (r= 0.54, P<0.01) and negatively with serum calcium (r =-0.65 and P<0.01).…”
Section: Serum Osteocalcin Concentrationsupporting
confidence: 92%
“…Similarly, another study indicated that 200 mg of soy isoflavones daily for 2 years did not prevent bone loss in menopausal women (55). Consistently, some studies have reported that treatment with isoflavones (aglycone equivalents), Trifolium pratense extract, and semelil (Angipars W) could not prevent a decline in BMD and had no significant effect on bone biomarkers and thus bone health (56)(57)(58)(59). According to previous studies and the present one, it seems that differences in the study populations and the lack of controlling for confounding factors such as soy or phytoestrogens consumption in the control group may have led to these inconsistencies.…”
Section: Discussionmentioning
confidence: 91%
“…Our study is the first animal study to assess the efficacy of Semelil (ANGIPARS) in osteogenesis alone and in combination with Bio-Oss, a popular bone graft substitute, in order to assess if this material can promote bone formation. Systemic application of ANGIPARS has no adverse effect on bone formation [ 21 ]. Results of an animal study showed that, during the study period, no significant difference existed in biochemical or hematologic parameters between the test and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Melilotus, coumarin, and flavonoids are the main constituents of ANGIPARS. It has been demonstrated that coumarin and vitamin K products increase osteogenic markers, that is, osteocalcin and alkaline phosphatase (ALP), and probably decrease urinary calcium and secretion of hydroxy proline (bone loss markers) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%